Applying a tiered environmental risk assessment framework to estimate the risk of pesticides to soil organisms in Latin America. (26th September 2022) - Tincani, Flavio; Cione, Ana Paola; Casallanovo, Fábio; Bottoms, Melanie; Alvarez, Tania; Loutseti, Stefania; Mackenzie, Richard; Thompson, Helen
Abstract: This work investigates the application of a tiered risk assessment scheme for soil organisms based on the risk quotient (RQ) and the toxicity exposure ratio (TER). Forty‐five pesticides registered in Latin America were chosen and the ecotoxicological endpoints for earthworms, Collembola, and microorganisms were collated. Tier I assessment was made on conservative assumptions in which no refinements were applied. There, 14 pesticides (31%) exceed the RQ regulatory trigger indicating unacceptable risk, whereas 27 (60%) indicate unacceptable risk on the TER approach. In a Tier II evaluation when refinement options such as foliar interception, field half‐life, and the dissipation following the peak estimated environmental concentration are considered, eight (18%) pesticides indicate unacceptable risk based on the RQ, and 15 (33%) indicate unacceptable risk based on the TER. A nonmetric multidimensional scaling evaluation was performed to understand the relevant characteristics involved in how each pesticide poses a risk to soil organisms. Based on the outcome of this analysis, we observed that, for a given pesticide, the combination of high persistence, low or no crop interception, and high toxicity are likely to require higher tier risk assessment. Refinement options can consider either or both the exposure and/or the effect side of the framework. Exposure refinements are potentially simpler and can be conducted with data already available to risk assessors, whereas effect refinements involving further testing with the organisms potentially at risk are still under discussion for intermediate and higher tiers. A sensitive, simple, and logical environmental risk assessment framework can be used to adequately identify risks based on the relevant protection goals that, in turn, will help to protect the desired soil multifunctionality of the ecosystem. We encourage academia and industry to further investigate these topics to provide the most scientifically robust and evidence‐based information to decision makers. Integr Environ Assess Manag 2023;19:446–460. © 2022 SETAC Key Points: Tiered environmental risk assessment frameworks are important in order to have a robust and science‐based evaluation of pesticides. As usual, the more conservative Tier I assessment was sufficient to filter out most pesticides, whereas the Tier II assessment proved to be effective in identifying risks and providing potential mitigations. It was noticed that the combination of high persistence, low or no crop interception, and high toxicity are likely to require a higher tier risk assessment; nonetheless, refinement options may consider either or both the exposure and effect route of the framework. Given that different regulatory triggers may provide different outcomes for the evaluation, it is important that triggers that sensibly reflect the assessed regulatory region are considered.